Land Use and Fiscal Competition - Thiess Büttner (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper explores the effects of fiscal competition on local land use. A theoretical analysis considers the tradeoff faced by a local government deciding about the amount of land made available for commercial or residential uses, when its expansion has adverse effects on the quality of life. The analysis shows that, in an environment with mobile tax bases, jurisdictions are subject to fiscal incentives to expand this land use. Fiscal redistribution through equalization grants, however, reduces these incentives. Based on the theoretical analysis, the effect of fiscal competition on commercial and residential land use is investigated empirically using a large dataset of German municipalities. In order to identify differences in the exposure to fiscal competition, I exploit institutional characteristics of the system of fiscal equalization to which these municipalities are subjected. This enables me to provide causal evidence using a regression discontinuity analysis. The results show that commercial and residential land use is expanded 2-3 times faster and agricultural land use declines more rapidly in municipalities exposed to fiscal competition.
Keywords: H71; R14; R52; Q26; 330; land use policy; natural amenities; urban sprawl; fiscal competition; fiscal equalization; regression discontinuity analysis